Estimation of the weights of wooden stacks of Pinus brutia Ten. And its changes with time under weather conditions of Al-Haffah site (Latakia –Syria) - علي وائل; يونس علي (Latakia University Journal -Biological Sciences Series, 2021)
This research aims to estimate the weight changes over time for the stacked wood logs of pinus brutia in the Al-Haffah site, which is 37 km away from Lattakia, and the weight changes of these stacks according to different weather conditions over a full year of the air drying process. This research also aims to estimate the extent of the effect of rainfall on the weights of these stacks, and finally to estimate the full moisture content by estimating the final weight after the stems have completely dried out. Several samples were taken by cutting several trees, weighing and stacking them in stacks under different conditions. The first stack was placed under a canopy of bricks to witness the drying process so that it won’t be affected by rainfall. The second stack was placed on a soil floor and the third stack was placed on an asphalt floor. The changes of stack weights were monitored over the course of a whole year and related to rainfall data of Al-Haffah site which was already obtained from Al-Haffa weather station. This study showed a rapid weight loss in the first period of the air drying process, as well as the presence of a clear effect of rainfall on the course of the drying process. Stocks lost about 45% of its weight after drying process run out.